Strategi Coping Stres Ibu Rumah Tangga dalam Menghadapi Kesulitan Ekonomi pada Masa Pandemi COVID-19 di Kota Bekasi - Nurtia Maharani; Artiarini Puspita Arwan (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2022)
Abstract: In 2020, the Covid-19 virus outbreak will affect a person's economy and health (physical or psychological). This situation makes some people feel stressed and have to survive in this situation. Everyone has a different way of dealing with the problems they face and religion has a role in helping to deal with problems for each of its adherents. This research uses a qualitative method with a case study approach. The research subjects consisted of 3 housewives. The data collection technique used a purpose sampling technique. Analysis of the data used is by means of data reduction, data presentation and drawing conclusions. The results showed that the coping strategies used were problem focus coping (planful problem solving and seeking social support) and emotional focused coping (positive reapraisal and self controlling). The description of the religiosity of the three informants in conditions of economic difficulty during the Covid-19 pandemic has a good level of religiosity, therefore the dimension of belief has a positive impact on worship and the behavior of the informants.Abstrak: Pada tahun 2020 merebaknya virus Covid-19 sehingga mempengaruhi ekonomi dan kesehatan (fisik atau psikologis) seseorang. Keadan tersebut membuat sebagian masyarakat merasa stres dan harus tetap bertahan dalam situasi ini. Setiap orang memiliki cara yang berbeda-beda terhadap masalah yang dihadapinya dan agama memiliki peran dalam membantu menghadapi permasalahan bagi setiap pemeluknya. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Subjek penelitian terdiri dari 3 ibu rumah tangga. Teknik pengambilan data menggunakan teknik purpose sampling. Analisis data yang digunakan yaitu dengan cara reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi coping yang digunakan yaitu problem focus coping (planful problem solving dan seeking social support) dan emotional focused coping (positive reapraisal dan self controlling). Gambaran religiusitas ketiga informan pada kondisi kesulitan ekonomi di masa pandemi Covid-19 memiliki tingkat religiusitas yang baik, oleh karena itu dimensi keyakinan memberikan dampak yang positif terhadap ibadah dan perilaku informan.